2022
DOI: 10.1128/spectrum.01727-21
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont-Induced Phagosome Changes Rather than Extracellular Discrimination Contribute to the Formation of Social Amoeba Farming Symbiosis

Abstract: Protists are single-celled, extremely diverse eukaryotic microbes. Like animals and plants, they live with bacterial symbionts and have complex relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Manipulation of phagosomes could also play a role in determining the contents of fruiting bodies. Paraburkholderia symbionts increase the pH of phagosomes, presumably to prevent host digestion of symbionts (Tian et al ., 2022). Similar modification of lysosomes is used by pathogens to evade human immune cells during infection (Isberg et al ., 2009; Leseigneur et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Manipulation of phagosomes could also play a role in determining the contents of fruiting bodies. Paraburkholderia symbionts increase the pH of phagosomes, presumably to prevent host digestion of symbionts (Tian et al ., 2022). Similar modification of lysosomes is used by pathogens to evade human immune cells during infection (Isberg et al ., 2009; Leseigneur et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We expected this result given the role of Paraburkholderia in causing hosts to carry food bacteria (DiSalvo et al ., 2015) and leave behind bacteria (Brock et al ., 2016b; Scott et al ., 2022). Infection with Paraburkholderia likely interferes with host digestion through modification of phagosomes (Tian et al ., 2022). This indigestion hypothesis is supported by our finding that Paraburkholderia infection did not affect development time (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This food carriage is mostly extracellular and varies by Paraburkholderia genotype and food bacterial species (Khojandi et al, 2019; Miller et al, 2020). Recent work has shown that Paraburkholderia symbionts inhibit phagosome acidification (Tian et al, 2022), suggesting that food carriage could be mediated by the creation of a more hospitable environment for other bacteria that get ingested. In the soil environment, however, many fruiting bodies contain microbiota, both with and without Paraburkholderia (Brock et al, 2018; Sallinger et al, 2021), and in our study, Paraburkholderia did not increase the diversity of this microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…This study used a model amoeba Dictyostelium discoideum QS9 for all experiments (Tian et al, 2022; Zhang et al, 2022). D. discoideum was grown from previously frozen spores on SM/5 agar plates (2 g glucose, 2 g BactoPeptone (Oxoid), 2 g yeast extract (Oxoid), 0.2 g MgCl 2 , 1.9 g KH 2 PO 4 , 1 g K 2 HPO 4 , and 15 g agar per liter) with food bacterium Klebsiella pneumoniae (obtained from the Dicty Stock Center) at 21°C.…”
Section: Methodsmentioning
confidence: 99%